An analysis of the amino acid content in the gingival fluid of both clinically healthy and inflamed gingiva - Uy, Jacqueline Joyce
Gingival fluids were collected from both clinically healthy and inflamed gingival of different subjects and of the same subject, using tapered filter paper strips. The amount of fluid was measured and related to the Gingival Index of the same gingival. The gingival fluids were subjected to acid hydrolysis, followed by two - dimensional paper chromatography for the analysis of amino acid content. Results showed that amino acids can be better detected in inflamed gingival because of greater volume of fluid, and that glutamine is the most common amino acid identified from the given samples.